Standardization of the speech tests used with cochlear implant patients - (:unkn) unknown (My University, 2007)
Objective: The aim of our study is to standardize the speech tests used in our clinic for the implanted patients. We standardized eight different tests for two different purposes: Assessment of the speech perception abilities of the cochlear implant candidates and evaluation of the progress of the cochlear implanted patients. Methods: Two groups of subjects (normal hearing and cochlear implanted) were given the eight different tests for standardization. The rate of correct answers of normal hearing and implanted groups was calculated and compared with "Instat" statistics program. Results: The results of speech reception tests developed in this study showed that the words in the lists were within the knowledge of the implanted patients. Content validity of the test was controlled. Alternative test forms were developed after item analysis. By doing so, we aimed to exclude the learning factor to a great extent. Conclusion: Standardized tests can be used for assessing the implant candidacy and evaluating the cochlear implantees' progress especially in the period following the implantation.
Keywords: Cochlear implant; Speech perception; Speech tests